2005
DOI: 10.1128/jcm.43.1.259-270.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sucrose-Negative Pasteurella multocida Variants, Including Isolates from Large-Cat Bite Wounds

Abstract: To validate the identification of Pasteurella multocida-like bacteria negative for acid formation from sucrose, including isolates from bite wounds caused by large cats, 17 strains were phenotypically and genotypically characterized. Phylogenetic analysis of partially sequenced rpoB and infB genes showed the monophyly of the strains characterized and the reference strains of P. multocida. The sucrose-negative strains formed two groups, one related to reference strains of P. multocida and the other related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
2
22
0
1
Order By: Relevance
“…These results confirm the high diversity showed by P. multocida isolates, previously reported by others (Christensen et al, 2004(Christensen et al, , 2005.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These results confirm the high diversity showed by P. multocida isolates, previously reported by others (Christensen et al, 2004(Christensen et al, , 2005.…”
supporting
confidence: 81%
“…In our study, a phenotypic diversity concerning ornithine decarboxylase, indole, and fermentation of mannitol and sucrose has been obtained (Table 1), all being characters that have been considered as essential for the identification of P. multocida at the species level (Larivière et al, 1992). However, two recent studies have demonstrated that several isolates from diverse origins that had been regarded atypical for these four phenotypic characters, they were all ascribed genetically to P. multocida by 16S rRNA gene sequencing and DNA-DNA hybridization (Christensen et al, 2004(Christensen et al, , 2005.…”
mentioning
confidence: 99%
“…5 In particular, P. multocida isolates can be very heterogeneous in their biochemical activity, appearing as variations in a single key character and making the unambiguous assignment of this organism on the species level quite problematic. 8 Moreover, discrimination between subspecies of P. multocida, namely P. multocida subsp. multocida, P. multocida subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Fowlpox virus was titrated on CK cells and the titre was calculated as 50% tissue culture infectious doses (TCID 50 ) per μl (Reed and Muench, 1938 Christensen et al (2005) proposed that this and similar isolates associated with large-cat bite wounds should be reclassified as a new taxon distinct from P. multocida. Should this taxon (taxon 45 of Bisgaard) be granted official standing in nomenclature, this organism's theoretical reactivity in the 5' Taq nuclease assay will have little bearing on the assay's usefulness as a diagnostic test for fowl cholera or P. multocida infections in production animals, as it would not be expected to occur in these animal species.…”
Section: Australia) Two Australian Field Isolates Of Avian Adenovirumentioning
confidence: 99%